Legal enforcement for chemicals uses for fishing in Wakatobi District. (February 2019) - Abdullah, L O D; Dewi, I K; Pratiwi, E T; Abdullah, R; Ilyas, A; Tambaru, R
Abstract: The chemicals using in fishing is very disturbing to the sustainability of the sea ecosystem. The primary objective of this research is to investigate the reasons behind the ineffectiveness of criminal law applied by the Wakatobi National Park Office for illegal fishing criminals who use chemicals to catch fish. The initial investigation revealed the law was not yet practical because there are individuals who were carrying out illegal fishing as a result of several factors which become the barrier. The results of research on law enforcement have found obstacles and support as follows: Inhibiting factors, namely: law factor, limitations of human resources, limitations of facilities and infrastructure, high costs, lack of expert witnesses, the absence of fisheries courts and lack of community awareness. Then supporting factors are law, government, police, and support from local, national and international governments.